Development of multiple intelligence ability tests of basketball in high schools - Huda, Nurul; Sukarmin, Yustinus; Dimyati, Dimyati; Setiawan, Risky (Journal of Education and Learning (EduLearn), 2024)
The study's objectives are to i) develop a test kit to determine the ability of multiple intelligences (MI) to play basketball in high school and ii) measure a student's MI test ability in playing basketball. The method used is the development of instruments with analysis, design, development, implementation, and evaluation (ADDIE). The study subjects comprised five schools in five districts in Yogyakarta, Indonesia. With a total sample of 1029 students. The results showed i) that test kits developed to assess students' MI abilities meet valid and reliable requirements. It can be seen from the validity of the contents of V-Aiken (0.96) and the validity of the construct, namely the loading factor 0.3. With the analysis of the item classically, it detects that the level of difficulty and differentiability of the problem is good and according to the criteria; ii) the results of MI capability measurements show 55% of capabilities with the "high" category, 35% with the "medium" category, and 10% with the "low" category.